A behavioral activation mobile application for depression among Korean young adults: a pilot study of multi-modal app usage patterns and clinical outcomes - Kang, Boyoung; Jung, Minjee; Kim, Ye-Seul; Han, Kyu-Man; Choi, Kee-Hong (Frontiers in Psychiatry, 2026)
IntroductionThe incidence of depression is increasing among Korean youth; however, access to care remains limited due to systemic and cultural barriers. Behavioral activation (BA) is a first-line treatment for depression; nevertheless, few digital interventions have delivered its core components or addressed cultural needs. Accordingly, this study evaluated the preliminary feasibility, potential clinical benefits, engagement, and fidelity of the B-ACT, a culturally adapted digital BA intervention for Korean young adults with depression.MethodsIn this single-arm seven-week pre-post study, 47 young adults with depressive disorders used the B-ACT app in hospital and community settings. This app delivered structured BA modules and activity tracking. Primary outcomes included changes in depressive symptoms, anxiety, the level of behavioral activation, and quality of life. Engagement metrics and positive activity data were also analyzed.ResultsThe participants showed significant reductions from baseline to post-treatment in depressive symptoms (BDI-II: -5.95, HDRS-17: -7.23, PHQ-8: -3.44) and anxiety (GAD-7: -2.47), along with increases in the level of behavioral activation (K-BADS: +11.50) and quality of life (SF-36 PCS: +6.62; MCS: +15.85). Post-treatment remission rates were 57.4% for HDRS-17, 27.7% for BDI-II, and 21.3% for PHQ-8, while response rates were 44.7%, 25.5%, and 21.3%, respectively. Greater participation in positive activities predicted a steeper decline in symptoms over time. Participants with more severe baseline depressive symptoms tended to show greater absolute reductions in symptom scores. The B-ACT showed high adherence and promising clinical change across hospital and community settings.ConclusionsThe B-ACT shows promise as a scalable and culturally responsive intervention for depression among young Korean adults. Participants demonstrated significant improvements in depressive and anxiety symptoms, the level of behavioral activation, and quality of life from baseline to post-treatment. Involvement in activities that elicit positive emotions emerged as a key therapeutic mechanism. Randomized controlled trials are needed to evaluate long-term outcomes and broader applicability.